Implementation Of The Yanbu'a Method To Improve Students' Qur'an Tahsin At The Darul Ma'arif Islamic Boarding School, Sekampung - Beti Wulandari; Hasyim As'ari; Irhamudin (Journal of Research in Islamic Education, 2026)
This study aims to analyze the implementation of the Yanbu'a method to improve the tahsin Al-Qur'an of students at Pondok Pesantren Darul Ma'arif Sekampung. The Yanbu'a method is one of the structured learning approaches developed to facilitate the reading of the Qur'an according to tajwid rules. This study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with teachers and students, and documentation of the learning process. Data analysis was carried out with interactive models including data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Yanbu'a method at Pondok Pesantren Darul Ma'arif Sekampung was carried out systematically through seven levels from basic to advanced. The effectiveness of this method is indicated by an increase in students' ability to read the Qur'an with correct makharijul huruf, proper application of tajwid rules, and improvement in reading fluency. Supporting factors include systematic curriculum, competent teachers, adequate facilities, and student motivation. While the inhibiting factors include the limited time allocation for learning and the variation in the initial ability of students. This study concludes that the Yanbu'a method can be an effective solution to improve the quality of tahsin Al-Qur'an in Islamic boarding schools. The implication of this study is that Islamic educational institutions can adopt the Yanbu'a method as a structured and systematic approach to improve Qur'anic recitation quality, provided that trained and certified teachers, adequate facilities, consistent evaluation systems, and strategies to enhance student motivation are in place.